Methodological features of an estimation of investment appeal of large regional transport projects - Eugeniy Kibalov; Olga A. Dyomina; Konstantin L. Komarov (European Regional Science Association (ERSA), 2002)
On the example of preinvestment researches of the Project of creation of a direct railway communication Mainland of Russia - Sakhalin island are considered the features of a comparative estimation of large transport projects in a context of development of regional, national and international transport networks . The opportunities of the scenarium approach to disclosing natural uncertainty in an estimation of ways of development of an environment around of the Project for a long (40 years) period of time are considered. The analysis of various circuits of calculation of public and a commercial effectiveness with reference to transport projects is carried out. Influence of organizational - economic mechanisms on economic efficiency is investigated. The methodical questions of an estimation of complex influence of transport projects on economy of regions and the countries as a whole are considered.
Keywords: 330